The Therapeutic Effect of Bilateral Alternating Stimulation Tactile Form Technology on the Stress Response - Serin, Amy; S. Hageman, Nathan; Kade, Emily (Journal of Biotechnology and Biomedical Science, 2018)
The application of bilateral alternating stimulation in tactile (BLAST) form technology, a non-invasive, somatosensory-based method, has been shown to modulate the electrical activity of brain networks that mediate the stress response, resulting in a stress-reducing effect in individuals with high reported levels of anxiety, such as post-traumatic stress disorder (PTSD). In this study, we examined archival data from a heterogeneous group of users (n = 1109) of BLAST technology via Touchpoints, a novel BLAST-based treatment modality, all of whom had high self-reported levels of stress and anxiety. Ratings of levels of emotional stress and bodily distress on a scale of 0 (no stress/distress) to 10 (worst stress/distress of one's life) before and after the application of Touchpoints for 30 seconds were entered into an app. Results showed a statistically significant reduction in the levels of both emotional stress and bodily distress, 62.26% and 50.502%, respectively, after 30 seconds of BLAST technology was applied. This demonstrates a clear benefit of BLAST on the stress response, reducing both emotional stress and disturbing body sensations. Recent work examining EEG changes after BLAST technology is applied suggests that BLAST may reduce sympathetic activation by reducing the electrical activity of key areas of the salience network. Further work will more precisely characterize the effects of BLAST, its potential clinical uses, and the mechanisms of actions behind it’s apparent stress-reducing effects.
Keywords: Bilateral Alternating Stimulation; Stress Response; Anxiety; Post-Traumatic Stress Disorder; Somatosensory Stimulation; Brain Networks